Measuring teacher self-efficacy: Validating a new comprehensive scale among Chinese pre-service teachers - Ma, Kang; Luo, Jiutong; Cavanagh, Michael; Dong, Jingjing; Sun, Meng (Frontiers in Psychology, 2023)
Challenges exist in the validating procedure and comprehensiveness of the existing TSE measurements, though advancements have been achieved. Also, less consistencies have been received regarding teacher self-efficacy measurement in Chinese context so that the study developed and validated a new comprehensive scale for this construct. A total of 854 Chinese pre-service teachers responded to 40 purposely selected teacher self-efficacy items, together with the Generalized Self-Efficacy Scale, the agreeableness subscale of the Big Five Inventory, and items on their effectiveness of teaching practicing and intention to be a teacher. Exploratory factor analyses revealed two distinct factors, one factor (Ethos) focused on the general school climate, harmony, and cooperation, as well as teachers' own professional development, the other (Teaching) focused on aspects of classrooms and student learning. Confirmatory and second-order factor analysis supported the existence of two factors and also indicated one overarching construct of teacher self-efficacy. Both domains were significantly correlated with general self-efficacy and agreeableness, with either moderate or low correlations. Significant differences in teacher self-efficacy for Ethos and Teaching were found between pre-service teachers who reported higher levels of effectiveness during their professional placement and greater intention to be teachers compared to those with lower self-ratings. In addition, a 20-item short version of the scale was developed, and the same factorial structure was confirmed. This study validated the two-factor structure of a newly developed teacher self-efficacy scale that covers domains both within and outside classroom teaching. Limitations and implications are discussed.